Recipe for disaster ebook - Angleberger, Tom (Didi Dodo, Future Spy, 2023)
Meet Didi Dodo. She's a dodo and a spy. Or she will be, once she's hired! Meet Koko Dodo. He's a dodo and a baker. He gives Didi Dodo her first case! Someone has stolen Koko Dodo's Super Secret Fudge Sauce for the Royal Cookie Contest! But don't worry. Didi Dodo has a daring plan to catch the culprit.